Pengembangan Software Menggunakan Model SDLC Guna Mencapai Keselarasan dengan Kebutuhan Pengguna - Fitria Anisa; Fauzi Syahputra Harahap; Harits Al Khosyi; Intan Permata Sari (Journal Of Informatics And Busisnes, 2024)
The Software Development Life Cycle (SDLC) details the activities that occur at each stage of the software development process. SDLC models are crucial in systematically structuring software, ensuring timely delivery and the desired quality. SDLC models provide a theoretical framework for software development, and due to the variety of models that exist, each SDLC has advantages and disadvantages that are used according to user requirements. Therefore, it is important to understand the needs in which an SDLC model will be implemented. In this research, various prominent SDLC models, such as the waterfall model, prototype, RAD, Spiral model, and Agile model, will be reviewed. As such, readers can use this research as a guide to find the model that best suits their specific needs.